BETWEEN JUDICIAL DISCRETION AND THE BEST INTERESTS OF THE CHILD: THE DILEMMA OF CHILD PROTECTION IN MARRIAGE DISPENSATION IN INDONESIA - Latifatus Zahra Az Zubaidi; Ahmad Fauzi; Ahbib Wildan Sholihi (Universitas Islam Indonesia, 2026)
Purpose – This study aims to analyze the normative paradox in the flexibility of marriage dispensations, which expands the subjectivity of judicial decisions due to the absence of substantive indicators of “urgent reasons” and parameters of the best interests of the child. In addition, this study examines the shift in the function of dispensations from the ultimum remedium to a response to social pressure. This study also evaluates its impact on the consistency of decisions and the effectiveness of the minimum age norm as an instrument of child protection. Methods – This study used a qualitative method with a normative legal approach. The research data consist of primary and secondary legal materials selected purposively based on their relevance and authority, with a focus on legal norms and judicial considerations related to marriage dispensation. Findings – This study confirms the existence of a normative paradox in the flexibility of marriage dispensation in Indonesia, where the mechanism, originally designed as a limited correction to the minimum age limit, has instead expanded the scope for subjectivity in judicial practice due to the absence of indicators regarding compelling reasons and operational parameters in the best interests of the child. This has resulted in inconsistent decisions and weakened child protection. Furthermore, the functional shift of dispensation from ultimum remedium to a response to social pressure has blurred the boundaries and has the potential to shift the law from an instrument of protection to a means of legitimizing child marriage practices. Research contribution/limitations – This study offers a conceptual framework for reorienting the practice of marriage dispensation towards child protection and substantive justice. However, this study does not fully accommodate the empirical perspectives of those directly affected by the disaster. Originality/value – The novelty of this study is that it positions marriage dispensation as a structural issue in family law, emphasizing the need for more accountable regulatory standards and judicial guidelines for the protection of children and justice.